Civilian Power In National Defence Sweden’s Model Of Integrated Societal Security - Raffi Muhammad Rahmawan; Muhammad Hadianto; Afrizal Hendra (International Journal of Business and Quality Research, 2026)
This article examines how Sweden integrates and mobilizes its civilian population as a core component of its revitalized Total Defence strategy in the 21st century. Building on concepts from Clausewitz’s Total War, and Holling’s Resilience Theory, the study analyzes Sweden’s shift toward a whole-of-society defence model capable of responding to hybrid, cyber, and infrastructural threats. Using a qualitative research method supported by a systematic literature review, the analysis reveals three key mechanisms of civilian mobilization: strengthened civil–military coordination, structured preparedness education, and the incorporation of voluntary organizations and private sector infrastructure into defence planning. The findings show that Sweden’s Total Defence now functions as an adaptive societal ecosystem in which civilians contribute directly to national resilience. This approach demonstrates how modern defence strategies can transform societal readiness into a strategic advantage.